2015
DOI: 10.1007/s11250-015-0916-2
|View full text |Cite
|
Sign up to set email alerts
|

Milk traits of lactating cows submitted to feed restriction

Abstract: Data from five experiments with dairy cows where feed was restricted to 0, 40, and 50% of the ad libitum amount, with 259 observations, were subjected to multivariate analyses to determine the effects of severity and duration of feed restriction on production, physical-chemical characteristics, ethanol stability, and somatic cell score of milk. A negative relationship was seen between the severity and duration of feed restriction with milk production, lactose content, titratable acidity, and milk stability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
0
17
0
4
Order By: Relevance
“…Differences in lactose and protein contents between milk with high stability and unstable milk are partially due to inadequate supply of nutrients, feeding of low-quality forages, metabolic or ruminal disturbances, and poor hygienic-sanitary characteristics of milk (Zanela et al, 2006;Barchiesi-Ferrrari et al, 2007;Marques et al, 2010a;Fagnani et al, 2014;Gabbi et al, 2016;Werncke et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in lactose and protein contents between milk with high stability and unstable milk are partially due to inadequate supply of nutrients, feeding of low-quality forages, metabolic or ruminal disturbances, and poor hygienic-sanitary characteristics of milk (Zanela et al, 2006;Barchiesi-Ferrrari et al, 2007;Marques et al, 2010a;Fagnani et al, 2014;Gabbi et al, 2016;Werncke et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several of milk traits (milk production, acidity, milk stability etc.) have been found to be negatively correlated with feed restriction in dairy cows (Gabbi et al, 2015). Lactating animals may seek to minimize the effect of nutrient restriction by adopting several adaptation strategies including increased mobilization of body reserved and decreased milk production.…”
Section: Milk Productionmentioning
confidence: 99%
“…Although having an association with bronchiolitis (Sawahata et al, 2010) and cytotoxic activity (Yunita et al, 2013), Sauropus androgynus is traditionally consumed by several Southeast Asian countries and is believed to be an enhancer of milk production during lactation (Bunawan et al, 2015). When feeding S. androgynus leaf extract to lactating mice, it enhanced the expression of two prominent genes (prolactin and oxytocin) regulating milk production and subsequently, increased milk production (Soka et al, 2010) suggesting their potential use to increase milk production in livestock ruminants (Gabbi et al, 2015).…”
Section: Milk Productionmentioning
confidence: 99%
“…The competitiveness of dairy products produced in Brazil with other commodities produced in the internal and/or external market is attributed, in part, to the use of forage plants as a source of nutrients for animals, which presents lower production costs in relation to concentrated inputs. However, forage production is not constant throughout the year in the country (Gabbi et al, 2016), especially in the semi-arid regions, which can impair the performance of animals.…”
Section: Introductionmentioning
confidence: 99%
“…of body tissues for maintenance, as well as present direct reactions in the productive and reproductive activities of the animal (Schütz et al, 2013), which leads to metabolic and adaptive changes in the body (Gabbi et al, 2016). Burke et al (2010) reported that, depending on the severity and time of feed restriction in lactating cows, there may be a reduction in milk production and, consequently, in the percentage of fat and protein and an increase in the somatic cell count (Fruscalso et al, 2013).…”
Section: Introductionmentioning
confidence: 99%